2002
DOI: 10.1039/b204316p
|View full text |Cite
|
Sign up to set email alerts
|

Application of ionic liquids as plasticizers for poly(methyl methacrylate)

Abstract: The room temperature ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate, [C4mim][PF6] was found to be an efficient plasticizer for poly(methyl methacrylate), prepared by in situ radical polymerization in the ionic liquid medium; the polymers have physical characteristics comparable with those containing traditional plasticizers and retain greater thermal stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(176 citation statements)
references
References 14 publications
7
167
1
1
Order By: Relevance
“…28 Imidazolium ionic liquids have been proposed as performant plasticizers for PVC, 29 and especially for PMMA. [30][31][32][33] In this paper, it is shown that highly luminescent flexible films can be obtained by doping europium(III) complexes into a composite material consisting of PMMA and the ionic liquid 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)-imide, [C 6 mim][Tf 2 N], as the plasticizer. Different europium(III) compounds, both ionic and non-ionic complexes, have been selected: [Eu(tta) 3 3 ], where tta is 2-thenoyltrifluoroacetonate, phen is 1,10-phenanthroline, nta is 2-naphthoyltrifluoroacetonate, dpa is 2,6-pyridinedicarboxylate (dipicolinate) and choline is the 2-hydroxyethyltrimethyl ammonium cation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…28 Imidazolium ionic liquids have been proposed as performant plasticizers for PVC, 29 and especially for PMMA. [30][31][32][33] In this paper, it is shown that highly luminescent flexible films can be obtained by doping europium(III) complexes into a composite material consisting of PMMA and the ionic liquid 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)-imide, [C 6 mim][Tf 2 N], as the plasticizer. Different europium(III) compounds, both ionic and non-ionic complexes, have been selected: [Eu(tta) 3 3 ], where tta is 2-thenoyltrifluoroacetonate, phen is 1,10-phenanthroline, nta is 2-naphthoyltrifluoroacetonate, dpa is 2,6-pyridinedicarboxylate (dipicolinate) and choline is the 2-hydroxyethyltrimethyl ammonium cation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It could be due to the fact that ionic liquids act both as plasticizer and as catalyst of the interface cross-linking reactions and thus speed up the cure reaction. 23,24 Curatives must dissolve in the rubber and diffuse to the active sites to react effectively for the efficient crosslinking of rubber. 25 It can be concluded that ionic liquid improved the dispersion of curing agents particularly zinc oxide in the polymer matrix, so their presence in rubber composites contributed to a considerable decrease of vulcanization time and an increase in the crosslinking efficiency.…”
Section: View Article Onlinementioning
confidence: 99%
“…Such a reduction of the mechanical stability can be explained by the plasticization of the polymer matrix with the IL. [71][72][73] The 'direct' casting of the films was performed because of a particular interest in industrial applications. However, additional experiments were then performed.…”
Section: Composite Filmsmentioning
confidence: 99%